Conventional culture media enriched with extracts of quinoa, amaranth and chia promotes the Staphylococcus aureus growth - Elizabeth Proaño-Pérez; Israel Manjarres-Raza; Cristian Carvajal-Tapia; Wilber Romero-Fernandez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2017)
Increasing the bacterial growth rate reduces the time getting the bacteria identification. This is helpful to choose an accurate and quick therapeutic strategy during microbiological infections, avoiding illness complications or in some cases the death. Here, we used bacterial growth method and we evaluated the growth of Staphylococcus aureus including an extract of Chenopodium quinoa, Amaranthus caudatus and Salvia hispanica in the routine culture media. Results show that adding these extracts, at low concentrations, have a protective effect against the cytotoxicity that could be generated by the oxidative stress product of the cellular metabolism of the bacteria growing in vitro and significantly increase the bacterial growth. The addition of these extracts to conventional culture media could improve bacterial growth during a bacteriological diagnosis and to reduce the time of pathogen identification.